2017
DOI: 10.1016/j.cub.2017.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Inter-adipocyte Adhesion and Signaling by Collagen IV Intercellular Concentrations in Drosophila

Abstract: Sheet-forming Collagen IV is the main component of basement membranes, which are planar polymers of extracellular matrix underlying epithelia and surrounding organs in all animals. Adipocytes in both insects and mammals are mesodermal in origin and often classified as mesenchymal. However, they form true tissues where cells remain compactly associated. Neither the mechanisms providing this tissue-level organization nor its functional significance are known. Here we show that discrete Collagen IV intercellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 52 publications
2
40
0
Order By: Relevance
“…In contrast to the accumulation of Col(IV) in SPARC protein-null larvae, overexpression of SPARC in a wild-type background resulted in a near absence of Col(IV) within the fat body. Consistent with a previous study (Dai et al, 2017), this loss of Col(IV) in the BM surrounding the fat body was observed in 3 rd instar larvae. In addition, individual adipocytes within the fat body were rounded and partially dissociated, as shown by SEM (Fig.…”
Section: Resultssupporting
confidence: 92%
“…In contrast to the accumulation of Col(IV) in SPARC protein-null larvae, overexpression of SPARC in a wild-type background resulted in a near absence of Col(IV) within the fat body. Consistent with a previous study (Dai et al, 2017), this loss of Col(IV) in the BM surrounding the fat body was observed in 3 rd instar larvae. In addition, individual adipocytes within the fat body were rounded and partially dissociated, as shown by SEM (Fig.…”
Section: Resultssupporting
confidence: 92%
“…When the MTOC is disrupted, secretion of collagen and other BM proteins are impaired as a consequence of plasma membrane overgrowth due to an imbalance in membrane trafficking from blocked retrograde endosomal trafficking. This is consistent with electron microscopic analysis of fat body plasma membranes following endocytic block, where the plasma membrane becomes highly convoluted and traps secreted BM proteins and prevents them from exiting the fat body surface (Dai et al, 2017). The ncMTOC is essential to provide trafficking conduits for endocytic vesicles to restrict plasma membrane growth, and a failure to restrict membrane growth traps BM proteins in the convoluted and thickened membrane and blocks their release ( Fig 38C).…”
Section: The Fat Body Ncmtoc Controls Nuclear Positioning and Plasma supporting
confidence: 84%
“…(Viking (vkg)) ( Figure 29A). A small fraction of secreted collagen IV is incorporated into fat body cell junctions as collagen IV intercellular concentrations (CIVICs) (Dai et al, 2017), but the majority is secreted, transported via the hemolymph, and deposited along with other BM components, like Perlecan (Trol), LanB1 and Nidogen (Ndg) at destination organs like imaginal discs and the brain ( Figure 29A) (Pastor-Pareja and Xu, 2011).…”
Section: The Fat Body Ncmtoc Is Essential For Basement Membrane (Bm) mentioning
confidence: 99%
“…They have also shown how BMs heal after injury [54,55] and how they regulate the immune response [56][57][58][59][60]. More recently, work in Drosophila has introduced a new role for BM proteins in intercellular adhesion [31].…”
Section: Introductionmentioning
confidence: 99%
“…BM is an ancient and highly conserved ECM that lines the basal surface of epithelial and endothelial tissues and surrounds muscles, adipose tissue, and nerves [26, 28,29]. Studies using Drosophila have made particularly strong contributions to our understanding of BM secretion and assembly [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45], and the role BMs play in shaping tissues during development [35,42,[46][47][48][49][50][51][52][53]. They have also shown how BMs heal after injury [54,55] and how they regulate the immune response [56][57][58][59][60].…”
Section: Introductionmentioning
confidence: 99%